A educação médica no Brasil a partir das Diretrizes Curriculares Nacionais de 2014: análise das produções científicas - CHOJI, Cristiano Hayoshi (2020)
This study is in line with Research Line 2: Training and action of the teaching professional and educational practices, as it investigates the institutional processes of teaching and learning involving theoretical studies and analysis of pedagogical practices related to Medical Education. Medical Education has historically evolved through significant changes in the conceptions and paradigms related to the professional to be trained, as well as with regard to the teaching action related to this professionalizing and socializing process. Thus, this research aims to analyze the academic-scientific productions published in the last five years by the Revista Brasileira de Educação Médica (RBEM), after the promulgation of the National Curriculum Guidelines for Medical Education (2014) that are articulated with propositions about the implementation of guidelines in medical education. This is a qualitative research that is characterized as an approach that makes it possible to carry out descriptions with details of the researched object, that is, the scientific productions of the last five years, relevant to the theme, published in the Revista Brasileira de Educação Médica (RBEM) that they cite its text the DCN 2014. Thus, for the execution of this bibliographic study, 117 articles were selected, of which it was found that 10 of them deal specifically with the 2014 DCN. Therefore, this study analyzed the 10 articles and found that there are few scientific publications focusing on the curricular implementation of the 2014 DCN in medical training, which demonstrates that it is still a dynamic and rugged evolution process, being even closer to a situation of methodological adequacy of teaching courses, than to the analysis of results in the professional training proposed by the new National Curricular Guideline for the medical course. The grouping of similar texts allowed the creation of the following classes analyzed based on the content of the articles: 1) Resistance to the new Curriculum; 2) Student Profile; 3) Pedagogical Process; 4) Course Proposal and Professional Practice 5) Curricular Integration.